Emerging and Recent Trends in Marketing: A path to Success for Modern Organizations - Ritesh Sharma (International Journal of Advanced Science and Technology, 2020)
This paper gives the views on current and the future trends of Marketing which can be beneficial to get success for the Modern Business organizations. Paper is secondary in nature which draws information from many secondary sources such as Magazines, newspapers, articles, researches, reports; internet etc .From the last many years, the Marketing field has undergone significant changes and transformation. It has moved from being producer-centric to customer-centric level. In the contemporary scenario, marketing maintenance oriented function is adopted, which is accepted by almost all the business organizations. As a outcome of significant changes which have happened in Marketing, there are many issues and questions which are raised and at the top of the list the question which arises as ‘ Whether Marketing has arrived at its final goal or destination or the journey will continue further?’ and if it is so, than what will be the next stage for Marketing? In setting the platform to discuss and explain the future of Marketing, we have described the journey of marketing since its inception. Marketing’s journey has been very important it has added value to organizations. To continue improving and evolving, Marketing has to adopt an inside and inside approach in which external environment plays a vital role which involves stakeholders, customers, shareholders etc. Keeping in mind what Marketing does inside the organization, we would discuss other detailed actions what Marketing might need, in order to add value, and to meet targets related to Marketing work which involves Marketing investments (Marketing function, Marketing practices, Marketing people, and Marketing analytics). For this we have presented a number of propositions which can be used by researchers and practitioners in terms of setting a platform which will become the guiding entity for future research and practices in this domain of Marketing.